Intralaryngeal paraganglioma workup and discussion of surgical approach. Issue 6 (2nd June 2020) - Abt, Nicholas B; Holcomb, Andrew J; Shroff, Stuti; Deschler, Daniel G
Abstract : Laryngeal paragangliomas are an uncommon presentation of head and neck paragangliomas, with laryngeal paragangliomas along with a synchronous paraganglioma being exceptionally rare. We present two challenging cases of laryngeal paragangliomas with extralaryngeal extension, completely resected through a transcervical approach without endolaryngeal disruption, with one case having synchronous bilateral carotid body tumours. Both patients had excellent results with complete tumour resection and no resultant functional impact. The surgical approaches for large laryngeal paraganglioma are discussed with considerations for endolaryngeal, transcervical and combined approaches as well as decision-making when approaching these rare lesions in the setting of synchronous head and neck paragangliomas.